2023
DOI: 10.1007/s40722-023-00283-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrofoil shape and turbine solidity on the wake energy recovery in cross-flow turbines

Abstract: Cross-flow turbines (CFTs) are arousing a growing interest to harvest both off-shore wind and tidal currents. A promising characteristic of CFTs could be a high power density in case of multi-device clusters or farms, achievable by shortening the distance between arrays as allowed by the fast energy recovery observed inside the wakes. However just few studies, only concerning symmetrical airfoils/hydrofoils, are found in the literature. By means of 3D Unsteady Reynolds Averaged Navier–Stokes (URANS) simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…For validation of wake development, we consider the same setup as used in the previous section. The simulation time is 21 turbine revolutions, analogous to what was done in [31], where the same experimental situation was studied using high-fidelity CFD simulations. In particular, [31] showed that at least 21 turbine revolutions are required to have a fully developed wake up to 8 diameters downstream of the turbine.…”
Section: Wake Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…For validation of wake development, we consider the same setup as used in the previous section. The simulation time is 21 turbine revolutions, analogous to what was done in [31], where the same experimental situation was studied using high-fidelity CFD simulations. In particular, [31] showed that at least 21 turbine revolutions are required to have a fully developed wake up to 8 diameters downstream of the turbine.…”
Section: Wake Validationmentioning
confidence: 99%
“…The simulation time is 21 turbine revolutions, analogous to what was done in [31], where the same experimental situation was studied using high-fidelity CFD simulations. In particular, [31] showed that at least 21 turbine revolutions are required to have a fully developed wake up to 8 diameters downstream of the turbine. All data described below are relative to the optimum TSR, i.e., 3.…”
Section: Wake Validationmentioning
confidence: 99%